Is level of knowledge, attitude and use of folic acid among pregnant women in Croatia a call for public health action? - Vitale, Ksenija (Array, 2009)
Knowledge, attitudes and practices of Croatian women regarding use of folic acid (FA) before and during pregnancy are assessed. Croatia has no current official recommendations for folic acid use for women who are planning pregnancy or are already pregnant, and there is no fortification of staple foods with FA. Among 603 women, 432 (71.7%) planned the current pregnancy, 306 (50.7%) did not take any vitamin supplement; 170 (28.2%) took some multivitamin supplements, and only 127 (21.1%) took FA supplements.